Pulling Effects in Immigrant Entrepreneurship: Does Gender Matter?. (1st January 2021) - Colombelli, Alessandra; Grinza, Elena; Meliciani, Valentina; Rossi, Mariacristina
Abstract: We examine whether the existing stock of immigrant firms induces more new firms of the same nationality in the same sector and province. We carry out the analysis by using Italian administrative data on the population of individual firms observed over the time window 2002–13. We find support for a strong attractiveness (pulling) effect, which significantly differs by gender, with female immigrant entrepreneurs showing a lower reactiveness to the existing stock of firms compared to their male counterparts. Also, we find that exposure to gender inequality matters for the degree of equality of the pulling effect between genders. Only for countries of origin with unequal gender opportunities do female immigrants show a lower pulling effect than their male peers. No difference in the effect between men and women is, instead, found with reference to the degree of gender inequality in the destination.